(3GdSjGSGJ GdfbOjI ddeJZjQGJ GdGbJUGOjI aj GdfXe GdeUQajI (B/s - (3gGTe, GSeGYjd eMeOs ((3GdGScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2011)
(3eGgjI GdfbhO hhXGFagG h CfhGYgG h GdfXe GdfbOjI , fTCI GdHfhc h JWhQ Gdaf GdeUQaj h Ndb GdfbhO h GdhOGFY h ejRGfjI GdHfhc GdJLGQjI , GdGQHMjI h GdSSjhdI h GdHfhc GdeQcRjI , JWhQ GdfXGe GdeUQaj GdeUQaj , GdfXQjI GdfbOjI GdJbdjOjI h GdJMdjd GdfbOj GdMOjK(B((3GdfbhO aj GdacQ GdcjfRj (B) (3h GdeYGUQ (B( (3GdfXQjI GdMOjKI dcejI GdfbhO (B) (3, GdBKGQ GdGbJUGOjI ddJZjQGJ aj bjeI GdfbhO , GdSjGSI GdfbOjI h CKQ JZjjQ bjeI GdfbhO Ydi GdONd Gdbhej , GdfbhO h GdOhQI GdJLGQjI h CNjQG GdeDSSGJ GdfbOjI HYO GdMQH GdYGdejI GdKGfjIs
Keywords: (3GdHfhcs; (3GdSjGSI GdfbOjIs; (3GdfbhOs